ANALISIS KESESUAIAN PENGELOLAAN LIMBAH PADAT MEDIS PUSKESMAS KORLEKO KABUPATEN LOMBOK TIMUR DITINJAU DARI PERATURAN MENTERI LINGKUNGAN HIDUP DAN KEHUTANAN NOMOR 56 TAHUN 2015 - Rilliyani, Dinda Rilliyani; haritini, husnayati; darmawan, muhammad iman (Fakultas Teknik Universitas Hamzanwadi, 2023)
Korleko Health Center is a community health center located in the East Lombok area. Based on the initial information obtained from the place is that the Health Center does not manage its own waste but uses the services of a second party through collaboration between B3 waste management service facilities. Korleko Health Center can produce solid medical waste ranging from ± 25 kg/month. Where if waste is not handled properly, it can cause accumulation in large quantities and can pose a risk of disease in the health center environment. There has been no related research that has conducted research on implementation techniques for solid waste management at the health care. Therefore, there is a need for an analysis of how solid medical waste is managed at the Korleko Community Health Center properly and correctly, and whether it is in accordance with the provisions of Minister of Environment and Forestry Regulation Number 56 of 2015. this research aims to analyze management of medical solid waste at the Communit y Health Center. The research method used is qualitative descriptive research. Data collection techniques include observation, open interview, and structured interviews. The results of this research shows that the medical solid waste management process is almost complete and implemented properly and correctly, but there are several aspects that have not been fulfilled, like no use of complete personal protective equipment such as aprons, special transportation lanes and moving waste that is sometimes not used and waste transport equipment that is not cleaned using a disinfectant compound